A Beamforming Algorithm for MIMO SWIPT Systems - Nguyen Duy-Nhat Vien (JOIV : International Journal on Informatics Visualization, 2018)
Efficient usage of energy resources is a growing concern in todayâ€™s communication systems. Energy harvesting is a new paradigm and allows the nodes to recharge their batteries from the environment. In this paper, we focus on the design of optimal linear beamformer for multi- input multi-output (MIMO) simultaneous wireless information and power transfer (SWIPT) system. We formulate the problem of maximizing the information rate while keeping the energy harvested at the energy receivers above given levels. Finally, simulation results demonstrate the efï¬ciency of the proposed algorithm.